Prosedur Penerbitan Sertifikat Safe Manning Kapal pada Kantor Syahbandar oleh PT. Gardatama Anugerah Segara Sejahtera Batam - Gunawan Arby Siregar; Nurmaliana Sari Siregar; Fadiyah Hani Sabila (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This paper discusses the activities of the ship agency business unit at PT. Gardatama Anugerah Segara Sejahtera Batam and the role of government agencies in issuing ship certificates, particularly the Safe Manning certificate at Batam port. The Safe Manning certificate is issued by the Directorate General of Sea Transportation for ship crews who meet national and international qualification and competency standards. The process of issuing this certificate requires supporting documents submitted by the shipowner or agency to the harbor master. Gardatama Anugerah Segara Sejahtera Batam has established good cooperative relationships with government agencies, private sectors, and ship owners, making it easier to process services and convey information related to ship needs. This research uses two methods: Field Research, which involves direct observation, and Library Research, which uses literature review as a data source.